The Effectiveness of Painting Therapy on Anxiety in Children with Attention-Deficit/Hyperactivity Disorder - Mardani , Farzaneh; Shafiabadi , Abdollah; Jafari , Asghar (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This study aimed to determine the effectiveness of painting therapy on anxiety in children with attention-deficit/hyperactivity disorder aged 7 to 10 years. Method: The research was quasi-experimental with a control group and pre-test, post-test, and one-month follow-up design. The statistical population included 60 students with attention-deficit/hyperactivity disorder identified in Islamshahr education. Using purposive sampling, 30 students were selected and randomly assigned to experimental and control groups. The experimental group received painting therapy intervention (Zadeh Mohammadi, 2010) weekly as a group in 10 sessions of 60 minutes. Both groups responded to the Children's Manifest Anxiety Scale (Reynolds and Richmond, 1978) before and after the intervention, and were re-evaluated one month later. Data were analyzed using repeated measures analysis of variance (ANOVA). Results: The results showed that painting therapy significantly reduced the level of total anxiety (F=38.91, P=0.001). Also painting therapy significantly reduced physical symptoms (F=5.35, P=0.021), anxiety (F=10.46, P=0.003), and extreme sensitivity/concentration (F=12.44, P=0.001) and these results were stable at the follow-up stage (p